Enhanced oxidation capacity driven by pollution-induced chlorine chemistry in the coastal atmosphere - Gaojie Chen; Ziying Chen; Yanru Zhang; Xiaolong Fan; Lingling Xu; Ziyi Lin; Xiaoting Ji; Jinsheng Chen (npj Climate and Atmospheric Science)
Abstract Reactive chlorine chemistry strongly influences the regulation of atmospheric oxidation capacity, thereby exerting profound impacts on the formation of secondary pollutants and air quality. However, current understanding of distributions and formation mechanisms of reactive chlorine species under the influence of air masses induced by pollution remains limited. In this study, we observed a significant increase in the concentrations of ClNO2, Cl2, and HOCl driven by pollution under the influence of continental air masses. By integrating field observations with model simulations, we revealed that unknown sources of these chlorine species are associated with nitrate photolysis and aerosol iron-mediated photochemical processes. The elevated levels of chlorine species promoted the increase in ROx radical concentrations, considerably intensifying the chemical formation of O3 and PAN and changing their sensitivity. These findings highlight the importance of anthropogenic pollutants in driving chlorine chemistry and provide scientific insights into its significance in regulating photochemical pollution.